Development and Validation of a Simple Risk Score for Undiagnosed Type 2 Diabetes in a Resource-Constrained Setting - Bernabe-Ortiz, A (2016)
The objective was to develop and validate a risk score for detecting cases of undiagnosed diabetes in a resource-constrained country. Methods. Two population based studies in Peruvian population aged ≥35 years were used in the analysis: the ENINBSC survey and the CRONICAS Cohort Study. Fasting plasma glucose ≥7.0 mmol/L was used to diagnose diabetes in both studies. Coefficients for risk score were derived from the ENINBSC data and then the performance was validated using both baseline and follow-up data of the CRONICAS Cohort Study.